Manual de experimentos de física utilizando um smartphone - Freitas, Renan Gustavo Beloni (2021)
This work aims to propose a physics experiment manual to be used in high school and elementary school, containing four low-cost scripts based on the acquisition of data through different sensors available on smartphones through a free application called Physics Toolbox . Based on the assumptions of David Ausubel's learning theory and how it can be applied in a teaching context based on experimental activities carried out in groups, it is expected that the application of the proposed scripts will bring greater meaning to the concepts covered in comparison with purely theoretical classes. , as well as encourage teachers who use the tools presented to develop their own proposals. Each script was designed to be completed in two classes, within a common classroom, with proposals that fall mainly in the investigative and verification fields. Its content presents, in addition to the methodology of the proposal and class for which it is intended, a brief introduction encompassing the related physics content and the specific sensor that will be used, with each of the manual's scripts being able to be worked independently of the others. The chosen themes are related to the content of Mechanics, Acoustics and Electromagnetism. Due to the impossibility of developing the work in the school environment due to the social distance imposed by the pandemic of COVID-19, the results of the experiments carried out by the author and fellow professors participating in the MNPEF are presented and discussed, together with their impressions related to the development of proposals. The analysis of these results demonstrates a great precision of the data obtained with the smartphone and minimum difficulty of execution, that added to the other functionalities of the employed applicationsuggests excellent possibilities of execution of the proposed experiments inside the school.